Introduzione ai Sistemi di Localizzazione Indoor - Maddio, Stefano (Manuali - Scienze Tecnologiche, 2017)
Introduzione ai Sistemi di Localizzazione Indoor ("Indoor Positioning Systems") is the second issue of the series "Quaderni del Dottorato di Ricerca in Ingegneria dell'Informazione" ("Issues of the PhD course in Information Engineering") of the University of Florence, as a didactic support to the PhD course bearing the same name. This issue is designed as an introductory text for those who want to test themselves in the emerging field of locating mobile vehicles in indoor environments, where satellite positioning services are absent or unreliable. Through its four chapters, the text reviews the main localisation methods, the corresponding algorithms, and the error propagation associated with the latter.